metaCage: Essays on and around Freeman Etudes, Fontana Mix, Aria - Parra Cancino, Juan; Andersson, Magnus; Kanno, Mieko; Brooks, William (Leuven Universitaire Pers Leuven, 2009)
metaCage investigates the musical practice of John Cage in four essays written by current ORCiM Fellows. Three works (Fontana Mix, Aria and Freeman Etudes) serve as threads that link the contributions, and a CD containing performances of these works, by the ORCiM Fellows, is included with the volume. The essays embrace both compositional practice, as viewed by musicologically-oriented performers Juan Parra Cancino and Mieko Kanno, and Cage's aesthetic framework, explored by practice-based musicologists Magnus Andersson and William Brooks.
Keywords: Cage, John -- 1912-1992; 20th Century (1901-2000); Artistic research; USA